Counseling and mental health interventions in sports: A systematic review of current practices and outcomes - Fitria, Linda; Ifdil, Ifdil; Muhammad Fahli Zatrahadi; Darmawati, Darmawati; Istiqomah, Istiqomah; Nur Adila Wafiqoh Zulvi; Nilma Zola; Fiky Zarya; Jeki Haryanto; Rima Pratiwi Fadli (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to highlight the importance of structured psychological intervention in supporting athletes’ recovery from injury, managing stress, and preventing future injuries. This study synthesised various relevant studies using a systematic literature review approach, with data sources from the Scopus database. The inclusion criteria included empirical studies, review articles, book chapters, and conference papers published between 1976 and 2024. The results of the study show that psychological interventions such as cognitive behavioral therapy (CBT), stress management programs, and goal-setting strategies contribute significantly to athletes’ mental resilience and physical recovery. Social support from family, coaches, and teammates also accelerated the rehabilitation process and increased recovery effectiveness. In addition, the integration of mental health strategies in training programs can reduce the risk of injury by managing competitive pressure and emotional stress. In conclusion, mental health counseling and interventions in sports are essential for improving the holistic well-being of athletes. This intervention not only helps with injury recovery but also serves as a preventive measure to maintain optimal performance. Collaboration between medical personnel and sports psychologists is necessary to ensure a comprehensive recovery plan covering both physical and mental aspects. This study emphasized the importance of implementing mental health strategies to improve athletes’ performance and well-being in competitive sports.